Evaluation of antioxidant, antimicrobial, antidiabetic, anti-tyrosinase, and neuroprotective effects of β-ionone: in vitro and in silico analysis - Jihane Touhtouh; Mustapha Laghmari; Taoufiq Benali; Tarik Aanniz; Mohamed Akhazzane; Khang Wen Goh; Waleed Al Abdulmonem; Abdelhakim Bouyahya; Gokhan Zengin; Khalil Hammani (Results in Chemistry)
β-Ionone is a bioactive phytochemical that has been extracted from many flowers, vegetables, and fruits. β-Ionone is an intriguing lead molecule from which several derivatives have been generated and exhibiting a variety of biological effects. Here, we investigated the β-Ionones’ antioxidant, anti-cholinesterases (AChE and BChE), anti-α-amylase, anti-α-glucosidase, and anti-tyrosinase activities. The antibacterial and antifungal effects were also studied. Moreover, in silico studies using molecular docking were carried out to understand the obtained results. The antioxidant activity performed by six different assays including phosphomolybdenum, CUPRAC, FRAP, DPPH, ABTS and metal chelating assay showed that β-Ionone exhibits a promising antioxidant activity. Besides, a good inhibition of AChE and BChE, as well as α-glucosidase, α-amylase, and tyrosinase was obtained. Molecular docking evidenced that β-Ionone correctly occupied the active site of the five studied enzymes through various kind of interactions which corroborate the in vitro outcomes. Moreover, in silico ADMET assessment showed that β-Ionone presented a good ADMET profile. Gram positive bacteria, specifically S. aureus (DIZ = 25 ± 1.5 mm; MIC = 6.25 mg/mL; CMB = 6.25 mg/mL) and B. cereus (DIZ = 21.5 ± 1 mm; MIC = 0.78 mg/mL; CMB = 0.78 mg/mL), showed greater susceptibility. Regarding Gram negative ones, P. aeruginosa exhibited also marked sensitivity (DIZ = 20.33 ± 1.5 mm; MIC = 12.5 mg/mL; CMB = 12.5 mg/mL). Additionally, β-Ionone can limit the growth of C. albicans (DIZ = 23 ± 1 mm; MIC = 1.56 mg/mL; CMB = 1.56 mg/mL). A bactericidal and fungicidal efficacy could be suggested as the MBC/MIC towards all the four inhibited pathogens was equal to 1. To sum up, data suggested that β-Ionone could have potential applications as an antioxidant, antimicrobial, and antifungal compound, as well as a potential inhibitor of tyrosinase, α-amylase, α-glucosidase, and cholinesterases. Furthermore, it can serve as a lead chemical in the creation of a new semisynthetic drug intended in order to treat numerous illnesses, including diabetes, Alzheimer’s disease, and pigmentation disorders.